РИТМІЧНІ ФОРМИ ТРИІКТОВОГО ДОЛЬНИКА В УКРАЇНСЬКІЙ ТА РУМУНСЬКІЙ ПОЕЗІЇ ПОЧАТКУ ХХ СТОЛІТТЯ - Paladian, Kristiniia (Casa Cărţii de Ştiinţă, 2019)
In the article the main attention is paid to the investigation of 3-ictus dolnik in Ukrainian and Romanian poetry at the beginning of the XXth century, establishing its metric status, marking its rhythmic forms, defining its origin. It is shown that both in Ukrainian and Romanian poetry 3- ictus dolnik is used simultaneously as a transitive metric form between syllabo-tonic and tonic versification and at the same time as one of the initial forms of tonic verse. At the source of dolnik in both poetries lies the versification technique of Western European, mostly German, sample of the verse. In Ukrainian dolnik the tendency is observed to polyforms and mixing of classical and non-classical traditions. The peculiarity of Ukrainian dolnik is the usage of trisyllable and disyllable rhythm. In Romanian dolnik the tendency is visible to classical and pure tonic systems of versi fication. The peculiarity of Romanian dolnik is the usage of trisyllable rhythm.
Rhythmic Forms of Three-ictus Dolnik in Ukrainian and Romanian Poetry at the Beginning of the XXth Century
Keywords: poetry; syllabo-tonic versification; tonic versification; dolnik; rhythmic forms of three-ictus dolnik